HybridAxes: An Immersive Analytics Tool With Interoperability Between 2D and Immersive Reality Modes - Seraji, Mohammad Rajabi; Stuerzlinger, Wolfgang (IEEE International Symposium on Mixed and Augmented Reality Workshops (Online), 2022)
Throughout the visual analytics process, users create visualizations with different dimensionalities. Research shows that in this process users benefit from being able to simultaneously see 2D and 3D modes of their data visualizations. Towards supporting this potential need, we introduce HybridAxes, an immersive visual analytics tool that allows the users to conduct their analysis at either end of the Reality-Virtuality continuum - either in 2D on desktop monitors or 3D in an immersive AR/VR environment - while enabling them to seamlessly switch between the two modes. We believe that by using our system, users will find it easier and faster to understand and analyze multi-dimensional data. An initial pilot test indicates positive trends in terms of users' performance time and usability metrics compared to the standalone desktop or AR/VR counterparts. Our preliminary results also suggest that users experience a lower cognitive load while task-switching between these virtuality modes. This reduction in mental effort causes them to perceive the system to be unobtrusive and pleasant to work with. Going forward, we plan to conduct more rigorous studies to verify our claims and to explore other research questions on this topic.